1991
DOI: 10.1002/oms.1210261118
|View full text |Cite
|
Sign up to set email alerts
|

Energy disposal in gas‐phase nucleophilic displacement reactions

Abstract: The partitioning of reaction exothermicity into relative translational energy of the products of gas-phase S, 2 (F-+ CH,CI) and nucleophilic aromatic substitution (F-+ C,H,CI) reactions has been investigated using kinetic energy release Fourier transform ion cyclotron resonance spectroscopy. The chloride product ion is observed to be highly translationally excited for the SN2 reaction, indicating a cold internal energy distribution for the products. For the chlorobenzene reaction the products are not generated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
38
2

Year Published

1998
1998
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 49 publications
5
38
2
Order By: Relevance
“…Thus, any P 10 formed would be uncompetitive in generating a second OH radical loss. 12 , from M 5 requires less energy than passing over the previous transition state, TS 4 ; hence there would be sufficient available energy to drive the first loss of OH radical (Tables 4a, 4b, Scheme 3). In addition, we performed CASSCF type calculations on M 5 and transition states for OH radical loss from even-electron M 5 : TS(M 5 -P 12 ) and TS(M 5 -P 13 ) yielding P 12 and P 13 , respectively (Table 4c).…”
Section: Theoretical Calculations: Proposed Mechanism Of Cyclizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, any P 10 formed would be uncompetitive in generating a second OH radical loss. 12 , from M 5 requires less energy than passing over the previous transition state, TS 4 ; hence there would be sufficient available energy to drive the first loss of OH radical (Tables 4a, 4b, Scheme 3). In addition, we performed CASSCF type calculations on M 5 and transition states for OH radical loss from even-electron M 5 : TS(M 5 -P 12 ) and TS(M 5 -P 13 ) yielding P 12 and P 13 , respectively (Table 4c).…”
Section: Theoretical Calculations: Proposed Mechanism Of Cyclizationmentioning
confidence: 99%
“…Cycloaddition reactions involving ion-molecule reactions in the gas phase and comparison to reactions in solution are the subjects of a recent review [10]. These and other examples show the utility of a mass spectrometer as a "reaction vessel" for investigating gas-phase reactions of potential synthetic utility [11][12][13][14]. The gas-phase cyclizations of the radical cations of several disubstituted aromatic compounds led to the discovery of new methods [15,16] for the synthesis of heterocyclic compounds.…”
Section: Introductionmentioning
confidence: 99%
“…[30][31][32][33] Also on mechanistic grounds, the ion-molecule reactions of anions with substituted benzenes bearing electron-withdrawing groups display a varied and rich chemistry in the gas phase. [34][35][36][37] The strong drive towards formation of anionic complexes displayed by polynitroaromatics used widely as explosives, such as trinitrotoluene, has been developed into a selective probe for their mass spectrometric detection. [38,39] Insights into the structural features of the anion interaction with an aromatic ring in an isolated state have been obtained in recent theoretical work.…”
Section: Introductionmentioning
confidence: 99%
“…These features are in good agreement with previous dynamics studies by Hase and co-workers. 13 From an experimental point of view, VanOrden et al 15 measured the energy distribution of the products in the gasphase S N 2 reaction ͑F − +CH 3 Cl͒ using Fourier transform ion cyclotron resonance ͑FT-ICR͒ spectroscopy, and found that the reaction proceeds with a large fraction of the exothermicity partitioned into the relative translational energy of the products.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] Nevertheless, fewer studies have addressed the role of solvation in these reactions. 16,17 From an experimental point of view, O'Hair et al investigated solvent effects on the S N 2 reaction of fluoride ion with methyl chloride and measured the product ions formed by the reaction F − ͑H 2 O͒ +CH 3 Cl.…”
Section: Introductionmentioning
confidence: 99%